Analysis of Organizational Culture in Improving the Performance of Educators and Educational Staff at Tanggamus Islamic Education College - Kurniawan, Heri (Malikussaleh University, Aceh, Indonesia, 2024)
This study aims to implement an organizational culture to support the achievement of set goals. Specifically, the study aims to analyze how implementing organizational culture enhances performance, as well as identify the factors that support and hinder this process. The research approach used in this study is descriptive qualitative. Collecting data from field studies is a crucial part of every research project. Data for the study was gathered through interviews, documentation, and observation. Educators and education staff may benefit from examining corporate culture, according to the study's findings. To be responsible, one must be free and independent, and one must also comprehend the duties of one another. Leadership: The organization's objectives and standards are laid out in a clear and concise manner. Incentives like pay raises and promotions are part of the reward system. How much horizontal or vertical communication there is depends on the communication system. The results of this study point to the importance of leadership in raising the efficiency and effectiveness of school staff and teachers. As a theoretical framework or point of reference, the results of this study can be used by universities to improve the performance of education workers and instructors. Furthermore, the researcher found that to establish a higher education institution operating in the Islamic field, universities must overcome both supportive and inhibiting factors. They also need the assistance of competent teaching and education personnel to implement quality enhancements, thereby creating a superior higher education institution.